Meningkatkan Keterampilan Membuat Tasbih dari Manik-manik Melalui Analisis Tugas bagi Anak Tunagrahita Ringan Kelas VIII di SLBN 2 Padang - Selvi Nofianti; Asep Ahmad Sopandi (Universitas Negeri Padang, 2018)
This research aims to determine the process of improving the skill in creating tasbih from beads through task analysis and to determine wheter task analysis method can improve the skill in creating tasbih from beads for students with mild intellectual disability in the 8th Grade of Special School Number 2 Padang. This study is a singgle subject research with desain A-B-A. The data analysis is in the form of visual analysis of graphich displays. The object of the research is an 8th grade student with mild intellectual disability. The target behavior of this reserch is for the student to be able to perform the steps in creating tasbih correctly. The variable measurement was in the form of the percentage of the number of intrument items. The results show that the student's skill in creating tasbih improved. In the baseline (A1) condition, classroom observation was conducted five times, and the persentage of the student's achievement was still low. In the intervention (B) condition, classroom observation was conducted seven times, and the percentage of the student's achievement increased from the percentage in the baseline (A1) condition. In the baseline (A2) condition, classroom observation was conducted five times, and the persentage of the student's achievement increased as compared to the initial ability. Based on these results, it is concluded that task analysis can improve the skill in creating tasbih from beads in a student with mild intellectual disability.